1980
DOI: 10.1530/jrf.0.0590259
|View full text |Cite
|
Sign up to set email alerts
|

Follicles explanted from pentobarbitone-treated rats provide a model for atresia

Abstract: Summary. Graafian follicles from rats treated for 1 or 2 days with pentobarbitone sodium (Nembutal)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 15 publications
4
36
1
Order By: Relevance
“…The amount of androstenedione used (0-1-1 0 µ ) might have saturated the system so that oestradiol synthesis plateaued. The fact that the 2-day delayed follicles were able to produce oestradiol in vitro at a level similar to controls (Table 1) contrasts with previous models using barbiturates (Uilenbroek, Woutersen & van der Schoot, 1980 ;Braw & Tsafriri, 1980;Terranova, 1981) in which oestradiol secretion by 2-day delayed follicles was reduced. The exogenous LH may maintain oestradiol secretion by the follicles through enhancement of aromatase ; however, the number of granulosa cells may be greater than in controls since the LH-treated follicles are larger.…”
Section: Resultscontrasting
confidence: 73%
“…The amount of androstenedione used (0-1-1 0 µ ) might have saturated the system so that oestradiol synthesis plateaued. The fact that the 2-day delayed follicles were able to produce oestradiol in vitro at a level similar to controls (Table 1) contrasts with previous models using barbiturates (Uilenbroek, Woutersen & van der Schoot, 1980 ;Braw & Tsafriri, 1980;Terranova, 1981) in which oestradiol secretion by 2-day delayed follicles was reduced. The exogenous LH may maintain oestradiol secretion by the follicles through enhancement of aromatase ; however, the number of granulosa cells may be greater than in controls since the LH-treated follicles are larger.…”
Section: Resultscontrasting
confidence: 73%
“…Inhibition of the LH surge by hypophysectomy or pentobarbital treatment causes the follicles to degenerate (Talbert et al, 1951;Braw and Tsafriri, 1980). The decrease in spontaneous apoptosis observed in isolated preovulatory rat follicles treated with hCG to stimulate the LH receptor may be mediated, at least in part, by endogenous production of pituitary adenylate cyclase-activating polypeptide (PACAP).…”
Section: Periovulatory Folliclesmentioning
confidence: 99%
“…It has been shown that atresia is associated with an increase in follicular progesterone production (McNatty, 1980;Braw & Tsafriri, 1980;Terranova, 1981 …”
Section: Inhibinmentioning
confidence: 99%